The effect of moderately halophilic bacteria supernatant on proliferation and apoptosis of cancer cells and mesenchymal stem cells - Sarvari, S; Seyedjafari, E; Amoozgar, M A; Bakhshandeh, B (Cellular and Molecular Biology, 2015)
Many drug discoveries and developing of their applications has originated from microbial metabolites. The most efforts in development of new drugs are concerned with anti-cancer agents that cause better treatment results, less side effects, and more economical production. Several anti-tumor drugs have been recently extracted from natural microbial products. Among these various microbial diversity, Marin bacteria and Archaea have been considered as important and efficient organisms to serve as manufacturers of diverse bioactive compounds. Moderately halophilic microorganisms isolated from saline ponds and lakes of Iran show high capability for production of bioactive compounds like enzymes, dyes and anti-cancer agents. In this research, nine moderately halophilic bacteria isolates were screened to evaluate their anti-cancer agent productivity. After five days of culture on suitable mediums, supernatant samples were tested for in vitro anti-proliferative activity against Human Umbilical Vein Endothelial Cells (HUVEC) while same concentrations of supernatants were examined for evaluating of proliferative activity against Adipose-derived Mesenchymal stem cells (MSCs). Both assessments were carried out by MTT assay and double PI and DAPI staining. GASX17, GBWy6 and GBPX3 isolates just induced HUVEC cell deaths and exhibited anti-proliferative activity while R2S12 not only reduced HUVEC cell proliferation but also enhanced proliferation of MSCs. R2S12 , GASX17, GBWy6 and GBPX3 isolates were characterized biochemically and six hydrophilic components were detected. This research established new bioactive compounds that could be used as an effective treatment in chemotherapy.